Episodes of Unemployment Reduction in Rich, Middle-Income, and Transition Economies - Freund, Caroline (World Bank, Washington, DC, 2014)
This paper studies the incidence and determinants of episodes of drastic unemployment reduction, defined as swift, substantial, and sustained declines in unemployment. Forty-three episodes are identified over a period of nearly three decades in 94 rich, middle-income, and transition countries. Unemployment reductions often coincide with an acceleration of growth and an improvement in macroeconomic conditions. Episodes are much more prevalent in countries with higher levels of unemployment and, given unemployment, are more likely in countries with better regulation. An efficient legal system that enforces contracts expeditiously is particularly important for reducing unemployment. The results imply that while employment is largely related to the business cycle, better regulation reduces the likelihood of high unemployment and facilitates a more rapid recovery in the event unemployment builds up.